Exploring the traditional knowledge and medicinal flora of the communities residing along North Eastern India-Pakistan borders - Arshad , Fahim; Ahmad, Waqas Ahmad; Shoaib , Muhammad; Harun, Nidaa; Fatima, Kaneez; Abbas, Zaheer; Jabeen, Sadia; Waheed , Muhammad (Ethnobotany Research and Applications, 2023)
Background: Ethnobotanical studies underpin the understanding of plant-people interaction in any geographical area along with the conservation strategies and priorities. The current study was carried out in the marginalized communities residing along the North Eastern Indo-Pak border of Depalpur and its adjoining areas of the Punjab Province, Pakistan. Methods: Snow-ball and random sampling techniques were employed for study participants. They were semi-structurally interviewed with open ended questions for the collection of desired data. Results: Altogether, 75 plant taxa were recorded in 68 genera and 32 families. The majority of them were wild herbs (86%), and whole plants (82%) were utilized frequently for drug preparations. Studied plants were reported to treat 40 ailments, however significantly used for fever (43 spp.) and gastrointestinal disorders (40 spp.). Conclusions: These findings endorsed the significant plant based knowledge of the border area populations. However, unprecedented rapid urbanization, economic development, and sociocultural dynamics challenged the retention of traditional knowledge. Profound decline was observed in the number of herbal practitioners, and their successors seem less interested in this field because of laborious jobs with low profit. Therefore, organic product development and the establishment of ethno species in home gardens and liaisoning with herbal industries may revitalize the existing traditional practices. Keywords: folk knowledge, border area, bio-cultural diversity, ethnoflora